In vitro B cell experiments explore the role of CD24, CD38, and energy metabolism in ME/CFS - Armstrong, Christopher W.; Mensah, Fane F. K.; Leandro, Maria J.; Reddy, Venkat; Gooley, Paul R.; Berkovitz, Saul; Cambridge, Geraldine (Frontiers in Immunology, 2024)
Introduction Disturbances of energy metabolism contribute to the clinical manifestations of myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). Previously, we found that B cells from ME/CFS patients have an increased expression of CD24, a modulator of many cellular functions including those of cell stress. The relative ability of B cells from ME/CFS patients and healthy controls (HC) to respond to rapid changes in energy demand was compared. Methods CD24, the ectonucleotidases CD39 and CD73, the NAD-degrading enzyme CD38, and mitochondrial mass (MM) were measured following cross-linking of the B cell receptor and costimulation with either T-cell-dependent or Toll-like-receptor-9-dependent agonists. The levels of metabolites consumed/produced were measured using 1H-NMR spectroscopy and analyzed in relation to cell growth and immunophenotype. Results Proliferating B cells from patients with ME/CFS showed a lower mitochondrial mass and a significantly increased usage of essential amino acids compared with those from HC, with a significantly delayed loss of CD24 and an increased expression of CD38 following stimulation. Discussion The immunophenotype results suggested the triggering of a stress response in ME/CFS B cells associated with the increased usage of additional substrates to maintain necessary ATP levels. Disturbances in energy metabolism in ME/CFS B cells were thus confirmed in a dynamic in vitro model, providing the basis for further mechanistic investigations.